Surface depletion and electrical transport model of AlInP-passivated GaAs nanowires - Chia, A. C. E. (2013)
Fabrication, current-voltage characterization and analytical modeling of an AlInP-passivated GaAs nanowire (NW) ensemble device are presented. During fabrication, sonication was used as a novel and crucial step to ensure effective contacting of the NWs. Current-voltage characteristics of the passivated NW devices were fitted using an analytical surface depletion and transport model which improves upon established models by implementing a non-uniform density of GaAs surface states across the bandgap and including a NW diameter distribution. Scanning electron microscopy, capacitance-voltage characterization and secondary ion mass spectrometry were used to fix key parameters in the model. A 43% decrease in surface state density was achieved upon passivation, corresponding to an impressive four order of magnitude increase in the effective carrier concentration of the NWs. Moreover, the thickest NWs in the ensemble were found to dictate the device characteristics, which is a behavior that should be common to all ensemble NW devices with a distribution in radius. As final confirmation of effective passivation, time-resolved photoluminescence measurements showed a 25x improvement in carrier lifetime upon passivation. The fabrication and passivation methods used can be easily implemented into future optoelectronic applications.